Menopause-related symptoms and symptom management of women in Manila - Mendoza, Ann Morrich M.; Macatangay, Nathaniel Bernard B.; Mahilum, Ella Mae Lolith P.; Mauleon, Lyka Monique G.; Mejia, Robert L.; Mendoza, Michelle Rose R.; Mercado, Carmela Louise C.; Victoria, Alexia Leigh D.
Millions of women experience the symptoms of menopause as they reach middle adulthood and are subjected to the consequences of decreased estrogen levels in the body. In the Philippines, the topic of menopause is slowly being given more attention on the population ages over the next few decades. This study (1) described the commonly- reported menopause-related symptoms (MRS) across stages of reproductive aging; (2) determined the level of bothersomeness of MRS; (3) determined the knowledge of women on menopause; (4) determined the relationship between knowledge and bothersomeness of MRS; and (5) determined the practices of women in managing their symptoms.